Extremity injuries and dementia disproportionately increase the risk for long-term care at older age in an analysis of German Health Insurance routine data for the years 2006 to 2010. Issue 1 (December 2016) - Barth, Alexander; Vatterrott, Anja; Zhou, Ying; Fink, Anne; Doblhammer, Gabriele
Abstract Background Extremity injuries (EI) and dementia are important causes of long-term care (LTC), but they can also cause each other and are often present concurrently. Mobility-limiting EI can increase the risk of dementia, and dementia increases the risk for falls, which are often the cause of EI. When EI and dementia are present together, they can increase their negative effect on long-term care risk. This study aims to assess the strength of this interaction and the role of different body regions and severities of EI regarding LTC risk. Methods We use Cox proportional-hazard models on LTC as dependent variable. EI (primarily fractures) and dementia (all types) are the central independent variables. We control for age, sex, rehabilitation and 18 relevant comorbidities. Analyses are based on health claims records for 2004–2010 for a random sample of about 122.000 insurants of Germany's largest public health insurance "AOK" aged 65+, about 25.000 of whom entered LTC. Results Without concurrent dementia, non-severe EI (NSEI) of the lower and both extremities and all kinds of severe EI (SEI) increase LTC risk (HR: hazard ratio with 95% confidence interval. Lower NSEI: HR = 1.09 [1.05–1.14]; both NSEI: HR = 1.36 [1.29–1.44]. Lower SEI: HR = 1.67 [1.57–1.79]; upper SEI: HR = 1.27 [1.19–1.37]; both SEI: HR = 1.94 [1.81–2.07]). Dementia alone increases LTC risk more than fourfold (HR = 4.23 [4.11–4.35]). Taking the interaction of EI and dementia into account, the concurrent presence of EI and dementia tends to increase the LTC risk more than expected for lower as well as upper NSEI and SEI. Summarily, when lower or upper EI and dementia are both present, the LTC risk tends to be higher than expected, suggesting synergistic effects. Conclusions EI and dementia are important independent risk factors for long-term care. When lower or upper EI and dementia are present together, the resulting long-term care risk is increased disproportionately. Since the concurrent presence of both conditions increases the risk for care need, and a working treatment for dementia is not in sight, preventing EI, lessening the impact of EI and improving the outlook after an EI could help to reduce LTC need in the coming decades.